“Local governance of workforce development” and vitalization of organizations in the United States: A paradigm shift in workforce development toward area-wide resilience - Soichiro MAEYAMA (AAOS Transactions)
The strategy and practice of “workforce development” has been viewed as a “paradigm-shifting” policy and practice in the U.S. labor market and local communities that goes beyond 20th century-vocational education and training with impact on local resilience. We obtained the following findings as a preparatory research: First, we have pursued in a preparatory way the connection between the mandatory of the Workforce Investment Act （WIA） 1998 and the substantive formation of workforce local governance with the case study of Seattle-King County. The results of a survey of key local person indicate that the effective establishment of local workforce governance of local area （SKCWDC） was not only due to federal directives （WIA of 1998）, but also to the pioneering efforts of the City of Seattle since the 1990s （new concept and coordinating agency/SJI organization）. The combination of federal policy and local management is a key element of the project. Secondly, we recognized the possibility that the “from welfare to work” policy perspective, which has long been seen in the U.S. as well as in Japan, may lead to a more structured and in-depth theorization of the dynamism of welfare and work that was occurring at the time.